Photosynthetic, Biochemical and Secondary Metabolite Changes in a Medicinal Plant Chlorophytum borivillianum (Safed musli) against Low and High Doses of UV‐B Radiation. (28th July 2022) - Jaiswal, Deepanshi; Pandey, Avantika; Agrawal, Madhoolika; Agrawal, Shashi Bhushan
Abstract: Plants are inevitably grown in presence of sunlight, therefore bound to be exposed to natural UV‐B radiation. Several studies have already been conducted with UV‐B and medicinal plants and only few studies showed dose dependent variation. The present study aims to find out the variations and adaptation in Chlorophytum borivillianum under two different doses of UV‐B radiation; ambient + low (3.2 kJm −2  d −1 ) and high (7.2 kJm −2  d −1 ) UV‐B dose, denoted as LD and HD, respectively. Reduction in photosynthetic rate was higher at HD, while plants receiving LD displayed nonsignificant variation. During vegetative and reproductive stage, significant reduction ( P ≤  0.001) in stomatal conductance was obtained when exposed to HD‐eUV‐B. F v / F m showed more reductions in HD‐eUV‐B (12.6%) followed by LD‐eUV‐B (7.9%). Low and high doses of UV‐B enhanced the anthocyanin content but the increase was significant in HD, indicates epidermal protection strategy by the plants. Under LD‐eUV‐B, the content of saponin, a major phytochemical constituent was enhanced by 26%. Phytochemical analysis of roots revealed reduction mostly in fatty acid components whereas the steroidal components (stigmasterol and sarsasapogenin) showed enhancement in response to LD. The study suggests the importance of LD‐eUV‐B in the stimulation of medicinal compounds in C. borivillianum . Abstract : Effects of low dose (LD) and high dose (HD) UV‐B on physiological parameters, UV‐B absorbing compounds, root biomass, ROS scavenging activities and saponin content (↑ less increase, ↑ ↑ high increase, ↓ decrease, ↓ ↓ high decrease).